2018
DOI: 10.2147/cmar.s154135
|View full text |Cite
|
Sign up to set email alerts
|

A favorable tumor size to define papillary thyroid microcarcinoma: an analysis of 1176 consecutive cases

Abstract: BackgroundThe optimal treatment strategy for papillary thyroid microcarcinoma (PTMC) has remained controversial. The purpose of this study was to provide a new reference value for PTMC to aid the selection of optimal management for minute lesions.Patients and methodsA pool of 1176 consecutive patients who met the inclusion criteria were ultimately enrolled in this study. The correlation of papillary thyroid carcinoma (PTC) tumor size and lymph node metastasis was analyzed. Receiver operating characteristic cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…16,17 Using ROC curve analysis, Gong et al determined 8.5 mm as a favorable tumor size to distinguish PTMC from PTC. 13 In the current study, we assessed tumor size by ROC curve analysis and found that primary tumor size (>6.5 mm) was significantly associated with CLNM. ETE is stratified into minimal ETE (mETE), identified by histopathological examinations, and gross ETE (gETE), detected by intraoperative findings.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…16,17 Using ROC curve analysis, Gong et al determined 8.5 mm as a favorable tumor size to distinguish PTMC from PTC. 13 In the current study, we assessed tumor size by ROC curve analysis and found that primary tumor size (>6.5 mm) was significantly associated with CLNM. ETE is stratified into minimal ETE (mETE), identified by histopathological examinations, and gross ETE (gETE), detected by intraoperative findings.…”
Section: Discussionmentioning
confidence: 81%
“…12 Previous studies demonstrated that PTMC with a larger tumor size might be biologically more similar to PTC. 13 However, the definition of PTMC (PTC measuring ≤10 mm in diameter) is still undecided. Therefore, establishing the most appropriate tumor size of PTMC to distinguish it from PTC is conducive toward determining the optimal treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 24 ) reported that 5.75 mm at preoperative ultrasound is the best cut-off value to predict the risk of central lymph node metastasis. In the study of Gong et al ( 25 ), including over 1,100 patients, a cut-off value of 8.5 mm was calculated based on receiver operating characteristics (ROC) curves: tumors with larger size demonstrated an aggressive behavior with a poorer prognosis, including, other than a higher incidence of lymph node metastasis, the presence of extrathyroidal extension, multifocality, and local recurrence. Xu et al ( 23 ) reported in a large series of over 3,000 patients with PTMC that a tumor size larger than 7 mm is strongly associated with a higher incidence of lymph node metastasis, suggesting in these patients a careful preoperative examination of central and lateral compartment and an aggressive surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 35 years, the incidence of papillary thyroid cancer (PTC) has tripled, largely due to the increasing incidence of papillary thyroid microcarcinoma (PTMC) [ 1 ]. These small cancers that measure 1.0 cm or less account for approximately 50% of the rise in PTC incidence [ 2 ]. Controversies still remain regarding thyroid resection and preventive central neck dissection, although PTMC has been shown to be cured by open surgery in the past [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%